PERSEPSI MAHASISWA PARIWISATA TERHADAP PERKULIAHAN PRAKTIK SECARA DARING: STUDI KASUS PROGRAM MANAJEMEN DIVISI KAMAR, POLITEKNIK PARIWISATA BALI - Ida Ayu Sri Puspa Adi; I Gusti Ngurah Agung Suprastayasa (JURNAL KEPARIWISATAAN, 2022)
This study aims to determine students' perceptions of online learning in practical courses at the Bali Tourism Polytechnic during the corona virus (COVID-19) pandemic. The students’ perceptions are limited to the aspects of teaching and learning, capabilities (lecturers' abilities), and facilities and infrastructure. The population in this study were all students of Room Division Management program of the Bali Tourism Polytechnic. The sample was taken using a purposive sampling technique which only focused on students who were taking practical courses in the Room Division Management program. Data were collected using online questionnaires and in-depth interviews with several students to obtain more detailed information. The data analysis technique used qualitative analysis consisting of data collection, data reduction, data presentation, and conclusion. The results showed that students' perceptions of online learning in practical courses are positive, with details of the teaching and learning aspects of 67%, the aspects of capabilities (lecturers' abilities) of 94%, and of the aspects of facilities and infrastructure of 79%. Based on the results of the interview, it was found that the problem lies in the devices owned by students that are not compatible to access online learning so it is difficult to do practicum at home.